Programação Baseada em Investigação-PBI: guia didático para professores. - Ferreira, Cristiano José (2018)
To help Computing Teachers that work directly with the Math students we create this didactical guide where they can find in a simple form, the foundations, methods and necessary resources to apply the PBI inside the classes. Abstract: Investigation-Based Programming (PBI) is a teaching-learning plan of computer programming aimed at college Mathematics students. The knowledge through PBI happens in a progressive way connected to examples that start with activities that stimulate investigation, discovering and independent learning. The PBI develops and improves skills to automate algebraic equations and the plotting graphs using programming language.